BCI Meeting 2005–workshop on signals and recording methods. - Jonathan Wolpaw; Loeb, Gerald E.; Brendan Z. Allison; Emanuel Donchin; do Nascimento, Omar Feix; Heetderks, William J.; Nijboer, Femke; Shain, William G.; Turner, James N. (IEEE transactions on neural systems and rehabilitation engineering : a publication of the IEEE Engineering in Medicine and Biology Society, 2006)
This paper describes the highlights of presentations and discussions during the Third International BCI Meeting in a workshop that evaluated potential brain-computer interface (BCI) signals and currently available recording methods. It defined the main potential user populations and their needs, addressed the relative advantages and disadvantages of noninvasive and implanted (i.e., invasive) methodologies, considered ethical issues, and focused on the challenges involved in translating BCI systems from the laboratory to widespread clinical use. The workshop stressed the critical importance of developing useful applications that establish the practical value of BCI technology.
Keywords: Brain-computer interface (BCI); electrophysiological signals; Rehabilitation

Brain-computer interface technology: a review of the Second International Meeting. - Theresa M Vaughan; Heetderks, William J.; Trejo, Leonard J.; Rymer, William Z.; Weinrich, Michael; Moore, Melody M.; Kübler, Andrea; Dobkin, Bruce H.; Niels Birbaumer; Emanuel Donchin; Wolpaw, Elizabeth Winter; Jonathan Wolpaw (IEEE transactions on neural systems and rehabilitation engineering : a publication of the IEEE Engineering in Medicine and Biology Society, 2003)
This paper summarizes the Brain-Computer Interfaces for Communication and Control, The Second International Meeting, held in Rensselaerville, NY, in June 2002. Sponsored by the National Institutes of Health and organized by the Wadsworth Center of the New York State Department of Health, the meeting addressed current work and future plans in brain-computer interface (BCI) research. Ninety-two researchers representing 38 different research groups from the United States, Canada, Europe, and China participated. The BCIs discussed at the meeting use electroencephalographic activity recorded from the scalp or single-neuron activity recorded within cortex to control cursor movement, select letters or icons, or operate neuroprostheses. The central element in each BCI is a translation algorithm that converts electrophysiological input from the user into output that controls external devices. BCI operation depends on effective interaction between two adaptive controllers, the user who encodes his or her commands in the electrophysiological input provided to the BCI, and the BCI that recognizes the commands contained in the input and expresses them in device control. Current BCIs have maximum information transfer rates of up to 25 b/min. Achievement of greater speed and accuracy requires improvements in signal acquisition and processing, in translation algorithms, and in user training. These improvements depend on interdisciplinary cooperation among neuroscientists, engineers, computer programmers, psychologists, and rehabilitation specialists, and on adoption and widespread application of objective criteria for evaluating alternative methods. The practical use of BCI technology will be determined by the development of appropriate applications and identification of appropriate user groups, and will require careful attention to the needs and desires of individual users.
Keywords: augmentative communication; Brain-computer interface (BCI); electroencephalography (EEG); Rehabilitation

Brain-computer interface technology: a review of the first international meeting. - Jonathan Wolpaw; Niels Birbaumer; Heetderks, W. J.; Dennis J. McFarland; Peckham, P. H.; Gerwin Schalk; Emanuel Donchin; Quatrano, L. A.; Robinson, C. J.; Theresa M Vaughan (IEEE transactions on rehabilitation engineering : a publication of the IEEE Engineering in Medicine and Biology Society, 2000)
Over the past decade, many laboratories have begun to explore brain-computer interface (BCI) technology as a radically new communication option for those with neuromuscular impairments that prevent them from using conventional augmentative communication methods. BCI's provide these users with communication channels that do not depend on peripheral nerves and muscles. This article summarizes the first international meeting devoted to BCI research and development. Current BCI's use electroencephalographic (EEG) activity recorded at the scalp or single-unit activity recorded from within cortex to control cursor movement, select letters or icons, or operate a neuroprosthesis. The central element in each BCI is a translation algorithm that converts electrophysiological input from the user into output that controls external devices. BCI operation depends on effective interaction between two adaptive controllers, the user who encodes his or her commands in the electrophysiological input provided to the BCI, and the BCI which recognizes the commands contained in the input and expresses them in device control. Current BCI's have maximum information transfer rates of 5-25 b/min. Achievement of greater speed and accuracy depends on improvements in signal processing, translation algorithms, and user training. These improvements depend on increased interdisciplinary cooperation between neuroscientists, engineers, computer programmers, psychologists, and rehabilitation specialists, and on adoption and widespread application of objective methods for evaluating alternative methods. The practical use of BCI technology depends on the development of appropriate applications, identification of appropriate user groups, and careful attention to the needs and desires of individual users. BCI research and development will also benefit from greater emphasis on peer-reviewed publications, and from adoption of standard venues for presentations and discussion.
Keywords: augmentative communication; Brain-computer interface (BCI); electroencephalography (EEG)

Brain-computer interface technology: a review of the first international meeting. - Jonathan Wolpaw; Niels Birbaumer; Heetderks, W J; Dennis J. McFarland; Peckham, P H; Gerwin Schalk; Emanuel Donchin; Quatrano, L A; Robinson, C J; Theresa M Vaughan (IEEE Trans Rehabil Eng, 2000)
Over the past decade, many laboratories have begun to explore brain-computer interface (BCI) technology as a radically new communication option for those with neuromuscular impairments that prevent them from using conventional augmentative communication methods. BCI's provide these users with communication channels that do not depend on peripheral nerves and muscles. This article summarizes the first international meeting devoted to BCI research and development. Current BCI's use electroencephalographic (EEG) activity recorded at the scalp or single-unit activity recorded from within cortex to control cursor movement, select letters or icons, or operate a neuroprosthesis. The central element in each BCI is a translation algorithm that converts electrophysiological input from the user into output that controls external devices. BCI operation depends on effective interaction between two adaptive controllers, the user who encodes his or her commands in the electrophysiological input provided to the BCI, and the BCI which recognizes the commands contained in the input and expresses them in device control. Current BCI's have maximum information transfer rates of 5-25 b/min. Achievement of greater speed and accuracy depends on improvements in signal processing, translation algorithms, and user training. These improvements depend on increased interdisciplinary cooperation between neuroscientists, engineers, computer programmers, psychologists, and rehabilitation specialists, and on adoption and widespread application of objective methods for evaluating alternative methods. The practical use of BCI technology depends on the development of appropriate applications, identification of appropriate user groups, and careful attention to the needs and desires of individual users. BCI research and development will also benefit from greater emphasis on peer-reviewed publications, and from adoption of standard venues for presentations and discussion.
Keywords: Algorithms; Cerebral Cortex; Communication Aids for Disabled; Disabled Persons; Electroencephalography; Evoked Potentials; Humans; Neuromuscular Diseases; Signal Processing, Computer-Assisted; User-Computer Interface

EEG-based communication: prospects and problems. - Theresa M Vaughan; Jonathan Wolpaw; Emanuel Donchin (IEEE transactions on rehabilitation engineering : a publication of the IEEE Engineering in Medicine and Biology Society, 1996)
Current rehabilitation engineering combines new prosthetic methods with recent developments in personal computers to provide alternative communication and control channels to individuals with motor impairments. Despite these advances, all commercially available systems still require some measure of voluntary motor control. Thus, these systems are not useful for individuals who are totally paralyzed. Electroencephalographic (EEG) activity may provide the basis for a system that would completely bypass normal motor output. EEG-based communication technology might provide assistive devices for individuals who have little or no reliable motor function. This paper reviews the prospects for and problems of EEG-based communication. It summarizes current approaches to development of this new technology, describes the major problems that must be resolved, and focuses on issues critical for its use by those with severe motor disabilities.
Keywords: Visual Perception